The prevalence of chronic dehydration and associated with cardiometabolic risks among agriculture and aquaculture workers - Ta-Chin Wang; Yuan-Hsiung Tsai; Jen-Tsung Yang; Ming-Shyang Lin; Ming-Shyang Lin; Yu-Chih Lin; Tung-Jung Huang; Tung-Jung Huang; Mei-Yen Chen; Mei-Yen Chen; Mei-Yen Chen (Frontiers Media S.A., 2023)
BackgroundChronic dehydration is associated with complications and mortality in acute ischemic stroke patients. Prior literature indicates that farmers and fishery workers are commonly affected by cardiometabolic diseases and there is a need for early prevention of stroke. This study explores the prevalence of dehydration and the association of cardiometabolic risk profiles in agricultural and aquaculture workers.MethodsWe conducted a community-based, cross-sectional study of agriculture and aquaculture workers in Yunlin County of Taiwan between August 1 and December 31, 2021. Data on demographic characteristics and health-related lifestyles were collected through one-on-one interviews using a questionnaire. The threshold for dehydration is defined as serum osmolality ≥295 mOsm/kg, and physiological biomarkers were collected from a collaborating hospital. Multivariable logistic regression analyses adjusted for demographic characteristics were performed to investigate the association between dehydration levels, cardiometabolic risks, and health-related behaviors.ResultsA total of 962 Taiwanese agriculture and aquaculture workers who were predominantly women (65%) with a mean age of 64 years (SD = 13.8) were enrolled. The findings showed a high prevalence of dehydration (36%), metabolic syndrome (44.5%), abnormal waist circumference (64.4%), and abnormal blood pressure (68.5%). Multivariate logistic regression demonstrated that dehydration was significantly associated with metabolic syndrome (p < 0.001), 10-year stroke risk prediction (p < 0.001), and an unhealthy lifestyle (p < 0.001).ConclusionThe prevalence of chronic dehydration was higher in Taiwanese agriculture and aquaculture workers, which was significantly associated with cardiometabolic risks and unhealthy lifestyles.